A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase matched second harmonic generation in a whispering gallery mode resonator - Fürst, Josef; Strekalov, Dmitry; Elser, Dominique Alexander; Lassen, Mikael; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Lasers and Electro-Optics/Quantum Electronics and Laser Science Conference: 2010 Laser Science to Photonic Applications, CLEO/QELS 2010, 2010)
We observed conversion efficiencies of 9% at 30 μW pump power in LiNbO3, as well as self-limiting effects at high powers. The continuous-wave pump at a wavelength of 1064nm and the second-harmonic feature Q > 107. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Nonlinear optics in crystalline: Whispering gallery resonators - Marquardt, Christoph; Strekalov, Dmitry V.; Fürst, Josef; Förtsch, Michael; Leuchs, Gerd (Optics and Photonics News, 2013)
CRIS-Team Scopus Importer:2022-06-05